H3N2 canine influenza virus-like particle vaccine with great protection in beagle dogs - Fei-fei Ge; Li-pin Shen; De-quan Yang; Xian-cao Yang; Xin Li; Hai-xiao Shen; Jian Wang; Shixin Huang (Microbiology Spectrum, 2024)
ABSTRACT In 2016, a distinct branch of H3N2 canine influenza virus (CIV) emerged, which has mutations related to mammalian adaptation and has replaced previously prevalent strains. This branch poses a risk of zoonotic infection. To prevent and control H3N2 CIV, an H3N2 virus-like particle (VLP) vaccine based on the insect cell baculovirus expression system has been developed in the study. The H3N2 VLP vaccine induced high titers of hemagglutination inhibition (HI) antibodies in nasal and muscular immunized beagle dogs. Meanwhile, the VLP vaccine provided effective protection against homologous virus challenge comparable to inactivated H3N2 canine influenza virus. In addition, the intranasal H3N2 VLP vaccine induced significantly higher Th1, Th2, and Th17 immune responses, respectively (p,0.05). Importantly, intramuscular injection of VLP and inactivated H3N2 virus has complete protective effects against homologous H3N2 virus attacks. Nasal immunization with H3N2 VLP can partially protect beagles from H3N2 influenza.IMPORTANCEA new antigenically and genetically distinct canine influenza virus (CIV) H3N2 clade possessing mutations associated with mammalian adaptation emerged in 2016 and substituted previously circulating strains. This clade poses a risk for zoonotic infection. In our study, intramuscular injection of the H3N2 virus-like particle (VLP) vaccine and inactivated H3N2 CIV confer completely sterilizing protection against homologous H3N2 canine influenza virus challenge. Our results provide further support for the possibility of developing VLP vaccines that can reliably induce immunity in animal species.